Condyloma Accuminata In Pregnancy Overlapping With Bacterial Vaginosis - Widyantari, Septiana; Rozita Maharani, Dinda; Koesandrini, Kinanthi; Setyaningrum, Trisniartami (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Human Papilloma Virus (HPV) 6 and 11 are most commonly detected in genital warts, known as condyloma acuminata. Bacterial vaginosis (BV) is the most frequent vaginal infection in women aged 15 to 44 years. There may be an association between condyloma acuminata and BV. Purpose : To report a case of condyloma accuminata in a pregnant patient with combination bacterial vaginosis. Case: A 24-year-old, 8-week pregnant woman came to the clinic with a chief complaint of multiple warts in the genital area since 3 months prior to the hospital visit. The bumps on the vulva were small, and at first only one but then spread to surrounding areas. The bumps were itchy and painful. Complaints of vaginal discharge or fluor albus of yellowish-white gray color, accompanied by itchy and a fishy odor that appeared three months ago and worsened in the last two weeks. Examination results led to the diagnosis of condyloma acuminata and BV in the patient. The patient's condition improved after being given 90% trichloroacetic acid (TCA), electrocautery, and metronidazole. Discussion: Pregnancy decreases cell-mediated immunity, which may decrease immune tolerance and local physiologic changes and ultimately increase HPV infection in pregnancy. HPV infection is associated with a vaginal microbiota imbalance, making pregnant women prone to vaginal infections such as BV. Conclusion: Condyloma accuminata and BV often occur in high-risk groups for sexually transmitted infections, one of which is pregnant women. It is necessary to screen for sexually transmitted infections (STIs) in pregnant women to prevent complications.